The CORE service improvement programme for mental health crisis resolution teams: results from a cluster-randomised trial. (June 2020) - Lloyd-Evans, Brynmor; Osborn, David; Marston, Louise; Lamb, Danielle; Ambler, Gareth; Hunter, Rachael; Mason, Oliver; Sullivan, Sarah; Henderson, Claire; Onyett, Steve; Johnston, Elaine; Morant, Nicola; et al.
Abstract : Background: Crisis resolution teams (CRTs) offer brief, intensive home treatment for people experiencing mental health crisis. CRT implementation is highly variable; positive trial outcomes have not been reproduced in scaled-up CRT care. Aims: To evaluate a 1-year programme to improve CRTs' model fidelity in a non-masked, cluster-randomised trial (part of the Crisis team Optimisation and RElapse prevention (CORE) research programme, trial registration number: ISRCTN47185233). Method: Fifteen CRTs in England received an intervention, informed by the US Implementing Evidence-Based Practice project, involving support from a CRT facilitator, online implementation resources and regular team fidelity reviews. Ten control CRTs received no additional support. The primary outcome was patient satisfaction, measured by the Client Satisfaction Questionnaire (CSQ-8), completed by 15 patients per team at CRT discharge ( n = 375). Secondary outcomes: CRT model fidelity, continuity of care, staff well-being, in-patient admissions and bed use and CRT readmissions were also evaluated. Results: All CRTs were retained in the trial. Median follow-up CSQ-8 score was 28 in each group: the adjusted average in the intervention group was higher than in the control group by 0.97 (95% CI −1.02 to 2.97) but this was not significant ( P = 0.34). There were fewer in-patient admissions, lower in-patient bed use and better staff psychological health in intervention teams. Model fidelity rose in most intervention teams and was significantly higher than in control teams at follow-up. There were no significant effects for other outcomes. Conclusions: The CRT service improvement programme did not achieve its primary aim of improving patient satisfaction. It showed some promise in improving CRT model fidelity and reducing acute in-patient admissions.